2012
DOI: 10.1016/j.mod.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Early embryonic lethality of mice with disrupted transcription cofactor PIMT/NCOA6IP/Tgs1 gene

Abstract: PIMT (also known as PIPMT/NCOA6IP/Tgs1), first isolated as a transcription coactivator PRIP (NCOA6)-interacting 96-kDa protein with RNA-binding property, possesses RNA methyltransferase activity. As a transcription coactivator binding protein, PIMT enhances the nuclear receptor transcriptional activity and its methyltransferase property is involved in the formation of the 2,2,7-trimethylguanosine cap of non-coding small RNAs, but the in vivo functions of this gene have not been fully explored. To elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…We recently showed that PIMT is essential for normal development and that disruption of PIMT results in embryonic lethality at day 3.5 [4]. To study the liver specific functions of PIMT, using Cre-LoxP strategy, we recently created a mouse strain in which PIMT was selectively deleted in liver (PIMT Ī”Liv KO mice)(Figure 8A and 8B) .…”
Section: Resultsmentioning
confidence: 99%
“…We recently showed that PIMT is essential for normal development and that disruption of PIMT results in embryonic lethality at day 3.5 [4]. To study the liver specific functions of PIMT, using Cre-LoxP strategy, we recently created a mouse strain in which PIMT was selectively deleted in liver (PIMT Ī”Liv KO mice)(Figure 8A and 8B) .…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila TGS1 is required for adult viability in both muscle and neurons (Komonyi et al, 2005;Provart et al, 2016), and loss of TGS1 function is lethal in the pupal stage. Disruption of tgs1 in mice similarly caused early embryonic lethality (Jia et al, 2012), establishing that TGS1 proteins are essential for many higher organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miR-3188 was found to reduce cell-cycle transition and proliferation in nasopharyngeal carcinoma by targeting mTOR mRNA and regulating the PI3K/ AKT signaling pathway through FOXO1 (60). In addition, it is possible that impaired processing of specific miRNAs in certain growth conditions may contribute to the embryonic lethality of TGS1-knockout mice (61).…”
Section: Exportin-1-dependent Mirna Biogenesis Occurs During Cellularmentioning
confidence: 99%